Lactate Transporters Mediate Glia-Neuron Metabolic Crosstalk in Homeostasis and Disease - Jha, Mithilesh Kumar; Morrison, Brett M. (Frontiers in Cellular Neuroscience, 2020)
Research over the last couple of decades has provided novel insights into lactate neurobiology and the implications of lactate transport-driven neuroenergetics in health and diseases of peripheral nerve and the brain. The expression pattern of lactate transporters in glia and neurons has now been described, though notable controversies and discrepancies remain. Importantly, down- and up-regulation experiments are underway to better understand the function of these transporters in different systems. Lactate transporters in peripheral nerves are important for maintenance of axon and myelin integrity, motor end-plate integrity, the development of diabetic peripheral neuropathy, and the functional recovery following nerve injuries. Similarly, brain energy metabolism and functions ranging from development to synaptic plasticity to axonal integrity are also dependent on lactate transport primarily between glia and neurons. This review is focused on critically analyzing the expression pattern and the functions of lactate transporters in peripheral nerves and the brain and highlighting their role in glia-neuron metabolic crosstalk in physiological and pathological conditions.